Isolation and Characterization of Rice Bran Protein Using NaOH Solution - Jannah, Akyunul (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2015)
The high protein content in rice bran potential to be developed into food. The purpose of this study was to isolate the protein in rice bran using NaOH solution with various concentration of 0.05; 0.1; 0.15; 0.2 M and characterization of functional properties. The results showed the concentration of 0.2 M NaOH produced the best results. The protein content obtained was 82%, stability ofÂ emulsion of 42% and 47% stabilty of foam.Â Keywords: NaOH, protein, rice bran